Poetic Bodies: Female Body Image, Sexual Identity and Arts-Based Research (LEARNing Landscapes, 2010)
This article reviews the use of a poetic form of analysis and representation of interview data collected on the topic of women’s body image and sexual identity. The researcher developed a tri-voiced poetic method that merges participant, researcher and literature voices. In this article the author advocates tri-voiced poems as a way of sharing researcher viewpoints, opening up dialogue, challenging stereotypes, and reaching and educating broad audiences.
Keywords: poetry; interview; sexual identity; participant; researcher; literature voice